Management of intestinal bleeding with single‐dose cyclophosphamide in Henoch–Schönlein purpura. Issue 3 (June 2015) - Uluca, Ünal; Ece, Aydın; Şen, Velat; Yel, Servet; Tan, İlhan; Karabel, Duran
Abstract In these case series, we report on six children (3 girls, 3 boys) aged 5–13 years with Henoch–Schönlein purpura (HSP) who developed severe gastrointestinal (GI) bleeding resistant to both 2 mg/kg or pulse (10–30 mg/kg) i.v. methylprednisolone. All patients responded to single‐dose (500 mg/m2) i.v. cyclophosphamide (CPA) and none of them developed new GI bleeding after CPA treatment. No patients required surgical intervention. Single high‐dose CPA may be beneficial in HSP with severe GI involvement, in which bleeding is non‐responsive to high‐dose steroids.